Protokolle des Ministerrates der Zweiten Republik, Kabinett Leopold Figl I Band 8: 25. November 1947 bis Jänner 1948 - Enderle-Burcell, Gertrude; Jerabek, Rudolf; Mueller, Wolfgang (Protokolle des Ministerrates der Zweiten Republik Österreich, 2017)
The Edition of the Minutes of the Cabinet Meetings of the first government of Leopold Figl constitutes an important contribution to historical knowledge on the early years of Austria's Second Republic and the reconstruction and renewal of the state and its political components after World War II. Volume 7 of the Edition encompasses the minutes of meeting No. 89 of November 25, 1947 to meeting No. 96 of January 20, 1948 as well as the accompanying minutes of the Wirtschaftliches Ministerkomitee from that time period. In terms of content, the discussions between the members of government documented therein pertain to a broad thematic spectrum, including matters of foreign, domestic and economic policy and reconstruction and the difficult relations between the Austrian government and the four great powers; there is particular emphasis on the ever-present matter of securing the basic level of nutrition for the Austrian and especially the Viennese population, on the ongoing deliberations on the Austrian State Treaty and on legislative measures to stabilize Austria's currency. The volume documents the many steps undertaken by the Austrian government to transform Austria once again into a sovereign state, integrated into the international community.